Frontal osteoplastic flap without frontal sinus obliteration for orbital roof decompression. (4th March 2021) - Kim, Matthew; Otten, Marc; Kazim, Michael; Gudis, David A.
ABSTRACT: Purpose : We describe a novel surgical approach for bilateral orbital roof decompression using a frontal osteoplastic flap without frontal sinus obliteration. This technique utilizes a combined external and endonasal endoscopic approach for wide exposure to the orbital roof bilaterally. We demonstrate this technique for the resection of a massive frontal fibrous dysplasia lesion in a healthy male with bilateral orbital roof involvement. The endonasal endoscopic portion of the technique includes a Draf III frontal sinusotomy (endoscopic modified Lothrop procedure) which precludes the need for frontal sinus obliteration, restores normal frontal sinus function, and allows for postoperative endoscopic surveillance. Methods : Report of novel surgical technique with video demonstration. Results : This technique for orbital roof decompression allows for removal of a frontal lesion, wide decompression of the bilateral orbital roof, and post-operative endonasal endoscopic surveillance of the cavity. The patient in whom we demonstrate this technique had complete resolution of his orbital symptoms and minimal residual fibrous dysplasia postoperatively. Conclusion : Bilateral orbital roof decompression for frontal lesions can be performed safely and effectively with a frontal osteoplastic flap without frontal sinus obliteration, restoring normal orbital and sinus function.